The Impact of Bond Market Access on Capital Structure – A study on US firms during periods of Loose and Tight Credit Market Conditions - Gomez, Dushan Angelo (2014)
Supply side determinants of capital structure have come to the fore since the influential paper by Graham and Harvey (2001). This paper attempts to underline the importance of these factors and uses whether a firm has a credit rating or not to proxy access to bond markets in order to test supply side factors on leverage. Thus the period tested for incorporates times where the supply of credit is loose as well as times where it is tight. The 2007 financial crisis is a part of the sample time frame and substantial arguments and evidence is provided in order to show that lending during the crisis was driven by supply factors rather than demand side factors. The results of the study provides evidence that firms with access to bond markets in general have higher leverage ratios than their counterparts without access to bond markets, after controlling for firm characteristics and macroeconomic factors. These findings are robust to alternative measures of access to bond markets.